Testing power poling by means of nordic ski ergometer and treadmill measurements - Bortolan, L.; Pellegrini, B.; Schena, F. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Several factors have contributed in the last few years to increase the importance of double poling (DP) technique in cross country ski. Evaluation and training of upper body power is usually performed by means of a traditional strength training apparatus even if the movements performed on this equipment are however quite different from the specific motion, The Nordic Ski Ergometer developed by CeBiSM has already demonstrate a good correlation between the average power measured with the ergometer and the performance in ski specific action (Bortolan, 2007). To investigate thoroughly the specificity of this ergometer the power measured by the ergometer during an multi load test has been compared with the power exerted during a double poling incremental test on a treadmill.